ChemInform Abstract: Selectfluor—Bu4NI‐Mediated C(sp3)—H Oxidation in Aqueous Media: Synthesis of Δ2‐Isoxazolines from Oximes. Issue 51 (December 2015) - Shi, Di; Qin, Hai‐Tao; Zhu, Chen; Liu, Feng
Abstract: This transition‐metal‐free approach generates Δ 2 ‐isoxazolines from oximes by radical‐mediated C(sp 3 )—H oxidation.